Surgical cognitive simulation improves real-world surgical performance: randomized study. Issue 3 (22nd May 2021) - Cragg, J; Mushtaq, F; Lal, N; Garnham, A; Hallissey, M; Graham, T; Shiralkar, U
Abstract: Background: Despite the acknowledgement of human factors, application of psychological methods by surgeons to improve surgical performance is sparse. This may reflect the paucity of evidence that would help surgeons to use psychological techniques effectively. There is a need for novel approaches to see how cognitive training might be used to address these challenges. Methods: Surgical trainees were divided into intervention and control groups. The intervention group received training in surgical cognitive simulation (SCS) and was asked to apply the techniques while working in operating theatres. Both groups underwent procedure-based assessment based on the UK and Ireland Intercollegiate Surgical Curriculum Programme (ISCP) before the training and 4 months afterwards. Subjective evaluations of SCS application were obtained from the intervention group participants. Results: Among 21 participants in the study, there was a statistically significant improvement in 11 of 16 procedure-based assessment domains ( P  < 0.050) as well as a statistically significant mean reduction in time to complete the procedure in the intervention group (–15.98 versus –1.14 min; P  = 0.024). Subjectively, the intervention group experienced various benefits with SCS, especially in preoperative preparedness, intraoperative focus, and overall performance. Conclusion: SCS training has a statistically significant impact in improving surgical performance. Subjective feedback suggests that surgeons are able to apply it in practice. SCS may prove a vital adjunct for skill acquisition in surgical training. Abstract : The aim was to address previous methodological flaws by objectively and subjectively assessing the effect of surgical cognitive simulation on both simulated and real-world surgical practice. Surgical trainees were randomized to receive training, and their simulated performance was assessed objectively using validated methods before and afterwards; the subjective effect this had on their real-world practice was also assessed. There were significant improvements in technical scores and speed following surgical cognitive simulation training, and real-world transferability over a prolonged period of time was demonstrated.